Teachers' and Students' Perspectives on Discovery Learning at Elementary School for Reading Comprehension - Fildatul Hammi; Muhammad Zainush Sholihin; Silmy Amelia (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2024)
This study aimed to investigate EFL learners’ and teachers’ perspectives on using the Discovery Learning method towards the students’ reading story comprehension. For this purpose, one teacher was interviewed and the thirteen students of Tambaagung Ares Elementary School were given questionnaires related to the benefit, interests, activities, and implementation strategies of Discovery Learning. Based on the analysis of the data collected, students and teachers had positive perspectives of Discovery learning to be implemented in Elementary school.